2015
DOI: 10.1093/jxb/erv476
|View full text |Cite
|
Sign up to set email alerts
|

Complex molecular mechanisms underlying seedling salt tolerance in rice revealed by comparative transcriptome and metabolomic profiling

Abstract: HighlightComprehensive analyses of phenotypic, metabolic, and transcriptome data from two genotypes with contrasting salt tolerance provided a more complete picture of the molecular mechanisms underlying seedling tolerance in rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 48 publications
7
64
3
Order By: Relevance
“…The mechanisms of salt tolerance in plants are very complex, which require coordinated expression of multiple stress responsive genes, and their encoding products can directly or indirectly protect plants. In plant, salt stress‐related genes or proteins form a complex regulatory network involving mitogen‐activated protein kinase cascade, reactive oxygen species (ROS) scavenging, defense‐related protein synthesis, glycolysis, tricarboxylic acid cycle, photosynthesis, amino acid metabolism, lipid metabolism and energy generation (Aghaei et al , Sobhanian et al , Zhang et al , Wang et al ). Plant hormones such as abscisic acid, auxin and jasmonic acid are key regulators in plant growth and salt stress response.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of salt tolerance in plants are very complex, which require coordinated expression of multiple stress responsive genes, and their encoding products can directly or indirectly protect plants. In plant, salt stress‐related genes or proteins form a complex regulatory network involving mitogen‐activated protein kinase cascade, reactive oxygen species (ROS) scavenging, defense‐related protein synthesis, glycolysis, tricarboxylic acid cycle, photosynthesis, amino acid metabolism, lipid metabolism and energy generation (Aghaei et al , Sobhanian et al , Zhang et al , Wang et al ). Plant hormones such as abscisic acid, auxin and jasmonic acid are key regulators in plant growth and salt stress response.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested the possibility that TU supplementation could accelerate Na + translocation towards shoots which is considered as one of the important defence mechanism to avoid built up of Na + toxicity in roots43. Recently, comparative evaluation of contrasting rice varieties have confirmed that tolerant varieties have better potential of translocating Na + from root-to-shoot44. Although, no significant change in K + was observed in shoot; in roots, it was maintained at significantly higher level of 1.42−, 2.13− and 2-fold in NaCl, NaCl + TU and TU treatments, respectively, as compared with control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High-throughput omic techniques have been used to investigate complex molecular response underlying salt tolerance in crops [24, 2631]. However, no related study has been done to reveal the genotypic differences of wild barleys in molecular responses to salt stress.…”
Section: Discussionmentioning
confidence: 99%